Pragmatics of Mathematics Education : Vagueness and Mathematical Discourse. - Rowland, Tim (RoutledgeFalmer, 1999)
In The Pragmatics of Mathematics Education, Tim Rowland examines students in the process of making and coming-to-know mathematics, focusing on the gap between conjecture and belief, between assertion and conviction.